Nutrition: The position in English to-day - M'Gonigle, G. C. M. (George Cuthberth Mura), -1939 (London : Industrial Christian Fellowship)
1936-11 1936 1930s 15 pages and more of the valuable protective foods, and less and less of the merely void-filling foods. The conclusion cannot be avoided and should not be shirked, that some millions of our population are improperly fed, and that this improper feeding is due in the main to lack of purchasing power, that it causes much preventable sickness, ill-health and suffering, and is not unconnected with the fact that large areas of the country, which are predominantly industrial, have higher death rates than more fortunately situated areas. The fact that the death rates are declining and that the standard of living has, in the past thirty years, risen should not blind us to the fact that things are still very bad, and that the evils are preventable. The fact that a death rate is less bad than it was thirty years ago does not make it good, but should be an incentive to make it good, not merely less bad. Simple economic facts as to nutrition are fully realised by farmers, who know that unless they feed their domestic animals properly they cannot expect a good yield of milk and eggs and wool and beef and mutton. The dairy farmer feeds his cows so that they get, not only a bodily maintenance ration, but in addition a milk-producing ration, which is calculated at so many pounds of food per gallon of milk. He knows that if the ration falls below the desirable quantity and quality his milk yield will fall. The mother of a young infant, in order to feed it as Nature intended it should be fed, must herself receive an adequate diet. A little simple arithmetic will show why it is that so many thousands of our poorer mothers are unable to breast-feed their infants, and why it is that State and Local funds must be expended on cows' milk for these unfortunate children. A pint of human 12 15X/2/217/2